2009
DOI: 10.1359/jbmr.081206
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin Antibody Treatment Increases Bone Formation, Bone Mass, and Bone Strength in a Rat Model of Postmenopausal Osteoporosis

Abstract: The development of bone-rebuilding anabolic agents for potential use in the treatment of bone loss conditions, such as osteoporosis, has been a long-standing goal. Genetic studies in humans and mice have shown that the secreted protein sclerostin is a key negative regulator of bone formation, although the magnitude and extent of sclerostin's role in the control of bone formation in the aging skeleton is still unclear. To study this unexplored area of sclerostin biology and to assess the pharmacologic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
531
4
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 701 publications
(588 citation statements)
references
References 41 publications
44
531
4
7
Order By: Relevance
“…The anabolic effect was less pronounced on the periosteal surface, and the decrease in BFR/BS in both groups during the study suggested that the surgery may have resulted in transient changes in periosteal bone formation independent of treatment. Consistent with the previous reports of the effects of Scl-Ab in rats (20) and cynomolgus monkeys, (21) bone formed during Scl-Ab treatment in this study was of normal lamellar architecture with no evidence of woven bone accumulation.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The anabolic effect was less pronounced on the periosteal surface, and the decrease in BFR/BS in both groups during the study suggested that the surgery may have resulted in transient changes in periosteal bone formation independent of treatment. Consistent with the previous reports of the effects of Scl-Ab in rats (20) and cynomolgus monkeys, (21) bone formed during Scl-Ab treatment in this study was of normal lamellar architecture with no evidence of woven bone accumulation.…”
Section: Discussionsupporting
confidence: 93%
“…These results differ from the anabolic effects of intermittent parathyroid hormone (PTH), which were associated with dose-dependent increases in cortical porosity in older OVX nonhuman primates. (33,34) Although the mechanism by which Scl-Ab reduced osteoclastic resorption is unclear, similar evidence for an antiresorptive effect with Scl-Ab administration was observed in OVX rats (20) and in healthy men and postmenopausal women. (22) However, inconsistent with the changes in histologic resorption, serum CTX was significantly increased in the Scl-Ab group at the end of the study (3.2 AE 0.3 ng/mL versus 2.5 AE 0.1 ng/mL, p < .05).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations